DISKRESI DALAM KEPEMIMPINAN PERGURUAN TINGGI YESUIT DI INDONESIA - Kristiyani, Titik (Sanata Dharma University, 2024)
Discernment is one of the important points in Ignatian leadership, i.e. leadership that refers to Ignatian spirituality. Higher education leaders are required to exercise discernment in solving problems as part of their responsibilities. This study aims to explore the practice of discretion among Jesuit higher education leaders in Indonesia. The research design was qualitative content analysis. The study involved 46 Jesuit higher education leaders in Indonesia as respondents. Data were collected through an open-ended online questionnaire with questions on issues requiring discretion, reasons/considerations, and skills needed to exercise discernment. Data were analyzed using thematic analysis through three steps, namely coding, determining themes, and determining categories based on similarity of themes. The findings of this study are: (1) reasons/ considerations in discernment include seven categories, namely: practicality, urgency, uncertainty, life values, predicting solutions, external support, and organizational development; (2) things needed in discretion include support, interpersonal skills, self-regulation, soft skills, values, experience, knowledge, and spirituality. The implication of this study for the development of leadership in higher education is the need to strengthen the leader capacity related to the themes in the findings of this study.